2019
DOI: 10.1158/1078-0432.ccr-18-0685
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 Inhibitor as a Novel Therapeutic Approach for Advanced Bladder Cancer Independently of RB1 Status

Abstract: Purpose: Bladder cancer is a clinical and social problem due to its high incidence and recurrence rates. It frequently appears in elderly patients showing other medical comorbidities that hamper the use of standard chemotherapy. We evaluated the activity of CDK4/6 inhibitor as a new therapy for patients unfit for cisplatin (CDDP).Experimental Design: Bladder cancer cell lines were tested for in vitro sensitivity to CDK4/6 inhibition. A novel metastatic bladder cancer mouse model was developed and used to test … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 58 publications
2
30
0
1
Order By: Relevance
“…We used 2 different approaches: on the one hand we used conventional cytomegalovirus promoter, Ad5-CMVcre, which targets most lung cell types (17) ( SI Appendix , Fig. S1 A – E ); on the other hand, we used an adenovirus (Ad5-K5cre) in which cre recombinase is under the control of keratin K5 promoter (18). This approach is based on the ability of proximal airway basal cells to self-renew and give rise to other cellular types (6, 7, 19) and has been reported to target lung basal cells (8).…”
Section: Resultsmentioning
confidence: 99%
“…We used 2 different approaches: on the one hand we used conventional cytomegalovirus promoter, Ad5-CMVcre, which targets most lung cell types (17) ( SI Appendix , Fig. S1 A – E ); on the other hand, we used an adenovirus (Ad5-K5cre) in which cre recombinase is under the control of keratin K5 promoter (18). This approach is based on the ability of proximal airway basal cells to self-renew and give rise to other cellular types (6, 7, 19) and has been reported to target lung basal cells (8).…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that the bladder cancer cells lines were sensitive to CDK4/6 inhibition regardless of RB status, suggesting a novel pathway. In the mouse model, CDk4/6 inhibition correlated with FOXM1 knockdown, and FOXM1 is an oncogenic driver in bladder cancer [125]. This study warrants further exploration of CDK4/6 inhibitors in bladder cancer in human studies, and also research into the link between CDK4/6 inhibitors and FOXM1 knockdown, which shows promise as a novel therapeutic tool.…”
Section: Insights In Biomedicine Issn 2572-5610mentioning
confidence: 67%
“…Levels of FOXM1 correlated with sensitivity to CDK4/6 inhibitors in Rb‐deficient bladder and small‐cell lung cancer cell lines. This observation led to a breakthrough in the treatment of advanced bladder cancer, which was previously considered unfit for treatment using existing drugs 85 …”
Section: Biological Consequences Of Pharmacological Cdk4/6 Inhibitionmentioning
confidence: 99%